Do Household Financial Behaviors affect Poverty in Indonesia?: Evidence from Indonesian Family Life Survey - Adhitya Wardhono; M. Abd. Nasir (Universitas Negeri Malang, 2022)
Poverty is a multidimensional phenomenon that can be measured by variety of approaches. The measurements of poverty based on consumption levels are not sufficient to explain various shortcomings faced by the poor. Household financial behavior that tends to be dynamic will indirectly affect household income patterns. Using data from the Indonesian Family Life Survey (IFLS) wave 5, this study aimed to identify the impact of household financial behavior on poverty in Indonesia. The results of analysis using Tobit Regression showed that the levels of financial vulnerability, financial literacy, education level, arisan or the rotating economy of savings and credit associations (ROSCAs), and total credit have a negative, significant relationship in influencing poverty. This means that when this variable increases, it will reduce poverty in Indonesia. Meanwhile, the location of residence, either in village or city, has a positive, significant relationship which implies that the location of residence has an impact on the poverty level in Indonesia.